مولانا محمد اکرم اعوانؒ بحیثیت مفسر قرآن: Maulana Muhammad Akram Awan (R.A) as an interpreter of the Holy Qur'an - Dr.Mubbasher Hassan Awan, (MEI, 2025)
The first interpretation of the Holy Quran is the supreme attributes of the Prophet. ﷺ The first witness of the sayings were the companions of the Prophet .ﷺ They presented tafsir according to the saying and actions of the Prophet ﷺ. Thus, this series is going on from the Tabi'in and Taba Tabi'in, (May Allah's mercy be upon them), to present time. Tafsirs have been written in every era and in every language, and Alhamdulillah, this series will continue till the day of judgment. Maulana Muhammad Akram Awan may God's mercy be upon him, was the Sheikh of the Silsila Naqshbandia Owaisiya and the founder of Tanzeem Al-Ikhwan Pakistan. He spent his life in the service of Islam. He was a multifaceted personality. Along with his academic and practical services in the field of Sufism, he also did outstanding work in the field of interpretation and presented three interpretations of the Holy Quran. In this research article, the discussion of his personality, as an interpreter of the Holy Qur'an, has been presented.